The sound analysis of the abstract triangular act outside of the anomaly measurement in the explanations of illiterate verbs is a balancing act in the light of modern linguistics (Journal of the College of Basic Education, 2022)
Some of the morphological versions of what is steady and measured in the language, counted by the early Arab scientists abnormal, and classified words that were not subject to the standards according to the number and quantity, and used several terms, including: little, rare, audible and abnormal, and all these terms - albeit somewhat different Its concept - is out of measure, whether anomaly, or Nadura, or from the audio, or a few . In these words, the laws of the language contradict the laws of language - especially morphology - and extract vocabulary from its standard form, in order to interfere in the orbit of another formula with the effect of its own sound law, so it is difficult to identify its causes and causes . We have found the abnormal in the abstract and abstract tripartite act, and did so, and it is possible to explain what came out of the verbal basis of the words according to the scientific analysis of the voices by following the voices of the word in terms of: exits, descriptions, and composition in The formula, and its effect before and after it, and the sites of the tone, and the consistency of sections, may be one of the reason for the departure of the formula from the standard rules, and may combine these reasons to create formulas that are desirable in the Arab taste is fluent, but they are within the rules of steady abnormal .